The Politics of Foreign Aid. - Wolfgang Mayer; Pascalis Raimondos-Møller (University of Copenhagen, Economic Policy Research Unit (EPRU), 1999)
Why do donor countries give foreign aid? The answers found in the literature are: (i) because donor countries care for recipient countries (e.g. altruism), and/or (ii) because there exist distortions that make the indirect gains from foreign aid (e.g. terms of trade effects) to be larger than the direct losses. This paper proposes a third answer to the above question, namely that aid is determined through the domestic political process of the donor country. The paper demonstrates how foreign aid affects the donor countrys income distribution and how, in a direct democracy, the majority of voters might benefit from foreign aid giving even though the countrys social welfare is reduced.
Keywords: 330